2016
DOI: 10.5530/pj.2017.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Physicochemical Evaluation of Leaves of Sphaeranthus indicus Linn

Abstract: Objective:To study the pharmacognostic characters of a medicinally important crude drug, Sphaeranthus indicus Linn. Methods: Various pharmacognostic parameters involved in organoleptic, microscopic, physicochemical, phytochemical and fluorescence evaluation were carried out. Results: The macroscopy study showed that the leaves was observed as sessile, obovate-oblong apex, tapered base, dentate margin, simple, serrate lamina, surface glabrous. The leaf microscopy showed the presence of diacytic stomata, unicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Similarly, an increased oxidative stress and mitochondrial dysfunction in MCF-7 cells treated with n-hexane fraction revealed the involvement of intrinsic pathway for the induction of apoptosis. Using GC-MS analysis, fats and oils, previously reported in the n-hexane fraction of S. indicus flowers [17], were also detected in the current study. However, detection of hexose sugars in the same fraction [17] could not be confirmed in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, an increased oxidative stress and mitochondrial dysfunction in MCF-7 cells treated with n-hexane fraction revealed the involvement of intrinsic pathway for the induction of apoptosis. Using GC-MS analysis, fats and oils, previously reported in the n-hexane fraction of S. indicus flowers [17], were also detected in the current study. However, detection of hexose sugars in the same fraction [17] could not be confirmed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Using GC-MS analysis, fats and oils, previously reported in the n-hexane fraction of S. indicus flowers [17], were also detected in the current study. However, detection of hexose sugars in the same fraction [17] could not be confirmed in this study. This variation in chemical composition of secondary metabolites might be due to various factors like extraction procedure, solvents, habitat, edaphic factors and climate conditions [13].…”
Section: Discussionsupporting
confidence: 77%
“…which may produce a solid basis for the authenticity of the plant and also to distinguish the seeds of C. viscosa seeds other similar species. 20,21 The macroscopic characters were examined to identify the seed of the C. viscosa. The powder characters of a drug are mainly used in the identification of the drug in the powder form.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The phytochemical study of this plant has been done several times by other authors and they concluded that the ethanolic and water extract of this plant showed the maximum number of components and the present research agreed with the authors research. [17][18][19][20][21]…”
Section: Discussionmentioning
confidence: 99%